PENERAPAN RELAKSASI OTOT PROGRESIF TERHADAP INTENSITAS NYERI POST OP SECTIO CAESAREA - Dany Setyogroho; Zumaroh Zumaroh; Adroni Adroni; Dewi Aisyah; Eka Sulistiyani; Wahyuningsih Wahyuningsih (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Reliable irrigation water supply is a crucial factor in supporting sustainable agricultural development, particularly in watershed areas where river discharge fluctuates significantly throughout the year. In many cases, excess water during the rainy season cannot be effectively utilized, while water shortages occur during the dry season, limiting agricultural productivity. This study aims to develop an irrigation dam planning scheme as a water storage and regulation structure capable of ensuring continuous irrigation water availability. The analysis includes hydrological assessment to determine water availability potential, calculation of irrigation water demand based on land characteristics and cropping patterns, and reservoir capacity planning in accordance with local topographic conditions. In addition, the technical design of the dam is evaluated through dimensional planning and stability analysis against sliding, overturning, and slope failure. The results indicate that the proposed dam has sufficient storage capacity to meet irrigation water demands and satisfies structural safety requirements. The implementation of this dam planning is expected to improve water resource utilization efficiency and strengthen agricultural sustainability within the studied watershed area.